2003
DOI: 10.1124/dmd.31.11.1337
|View full text |Cite
|
Sign up to set email alerts
|

CONSTITUTIVE EXPRESSION OF VARIOUS XENOBIOTIC AND ENDOBIOTIC TRANSPORTER mRNAs IN THE CHOROID PLEXUS OF RATS

Abstract: ABSTRACT:The aim of this study was to quantitatively determine the constitutive expression levels of various transporter mRNAs in rat choroid plexus. To provide a reference for the relative expression levels, the expression of various transporter mRNAs in choroid plexus were compared with that in liver, kidney, and ileum. The mRNA levels of multidrug resistance protein (Mrp)1, 2, 3, 4, 5, and 6; multidrug resistance (Mdr)1a, 1b, and 2; organic anion transporting polypeptide ( The target-organ toxicity of any x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
126
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(138 citation statements)
references
References 43 publications
11
126
1
Order By: Relevance
“…This might explain the seemingly lack of impact of AamOatp silencing on early tick-feeding parameters, attachment onto host skin and beginning to feed. Consistent with vertebrate Oatp/OATP genes that show multiple tissue expression patterns (St-Pierre et al, 2002;Gao et al, 2005;Choudhuri et al, 2003), our RT-PCR expression analyses data revealed that AamOatp mRNA is both constitutively and ubiquitously expressed, as it was it is expressed in all tested organs of ticks that fed for 1-7 days. Transcriptional regulation of tick genes has been shown in response to blood meal feeding, being either shut down or induced, up-or down regulated (Leboule et al, 2002a;Leboule et al, 2002b;Mulenga et al, 2001;Rudenko et al, 2005).…”
Section: Discussionsupporting
confidence: 51%
“…This might explain the seemingly lack of impact of AamOatp silencing on early tick-feeding parameters, attachment onto host skin and beginning to feed. Consistent with vertebrate Oatp/OATP genes that show multiple tissue expression patterns (St-Pierre et al, 2002;Gao et al, 2005;Choudhuri et al, 2003), our RT-PCR expression analyses data revealed that AamOatp mRNA is both constitutively and ubiquitously expressed, as it was it is expressed in all tested organs of ticks that fed for 1-7 days. Transcriptional regulation of tick genes has been shown in response to blood meal feeding, being either shut down or induced, up-or down regulated (Leboule et al, 2002a;Leboule et al, 2002b;Mulenga et al, 2001;Rudenko et al, 2005).…”
Section: Discussionsupporting
confidence: 51%
“…However, there is no direct evidence demonstrating the expression of OCT2 in the CP or its localization to the apical membrane. Gene profiling work by us and others showed very low expression of Oct2 in rodent CPs (35). Here, using quantitative real time PCR, we clearly showed that in both human and mouse CP tissues, PMAT/Pmat is the dominating monoamine/OC transporter, whereas other functionally related transporters, including OCT1, OCT2, OCT3, MATE1/2, SERT, DAT, and NET, are minimally expressed (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…23 Similarly, a diet enriched with 0.3% DCA predominantly increased cholic acid and the taurine conjugates of both species. 52 Therefore, it is reasonable to assume that the effects of cholic acid or DCA feeding on the neurological decline because of acute liver failure may not solely be because of the The Mechanism of Action of Bile Acids in the Brain Involves ASBT-Dependent Uptake and Activation of FXR Circulating bile acids can gain access to the brain via two known mechanisms. First, bile acids can be transported across the BBB through the bile acid transporters found in the choroid plexus.…”
Section: Strategies To Deplete or Alter The Composition Of The Bile Amentioning
confidence: 99%
“…First, bile acids can be transported across the BBB through the bile acid transporters found in the choroid plexus. 52 Second, another route of entry is via the diffusion of bile acids through an increasingly permeable BBB. We, and others, have demonstrated that the BBB is impaired in models of acute and chronic liver damage.…”
Section: Strategies To Deplete or Alter The Composition Of The Bile Amentioning
confidence: 99%